Best management practices for hatcheries culturing African catfish - Isa, Suleiman (WorldFish, 2023)
This document was put together with the aim of providing best management practices (BMPs) to small and medium-sized hatcheries producing African catfish (Clarias gariepinus) fingerlings or juveniles. Adhering to these practices will not only increase efficiency and profit for farmers but will also minimize losses and key negative environmental and social impacts of African catfish hatcheries.